Mindfulness-based cognitive therapy as a clinical intervention with psoriasis patients through the lens of the clinically modified Buddhist psychological model: a qualitative study. Issue 9 (20th October 2020) - Maddock, Alan; Hevey, David; D'Alton, Paul; Kirby, Brian
ABSTRACT: Coping with a chronic illness such as psoriasis can be very stressful experience for patients. A psoriasis patient's cognitive appraisal of their condition, definition of adaptive tasks, and selection of coping skills are influenced by the person, by aspects of the transition or crisis, and by their environment. Mindfulness-based interventions are theorised to have the capacity to enhance these factors and the mental health and wellbeing of patients with various physical and mental health issues. The change process involved with mindfulness is a complex one, and it remains unclear what the mechanisms of change are. In order to explore the potential mechanisms of mindfulness and styles of coping, which may explain changes in physical and mental health outcomes of psoriasis patients, semi-structured qualitative interview data was collected from 10 psoriasis patients who had attended at least seven of the eight weeks of a Mindfulness-based Cognitive Therapy intervention (MBCT). This study found that through MBCT group participation, this group of psoriasis patients was able to develop enhanced approach oriented coping skills. The development of these skills reduced the extent to which participants engaged in negative thinking, and also led to improved physical and mental health. This study gives support to the promising potential of MBCT as an effective intervention to improve psoriasis patient physical and mental health. This study also provides support the usefulness of a clinically modified Buddhist psychological model as an aid to understanding how these improvements might be achieved, with the relative importance of individual approach oriented mechanisms of action being different for different people.